Colorectal Cancer and Polyps in Diverticulosis Patients: A 10-Year Retrospective Study in 13680 Patients. (1st December 2019) - Abu Baker, Fadi; Z'cruz De La Garza, Jesus Alonso; Mari, Amir; Zeina, Abdel-Rauf; Bishara, Amani; Gal, Oren; Kopelman, Yael
Abstract : Introduction . Shared by certain epidemiological and etiological characteristics, diverticulosis and colorectal cancer (CRC) as well as colonic polyps has long been linked. This association was studied in several heterogeneous studies but has reported inconsistent results. Clarifying the association is clinically relevant for endoscopist awareness and potential modification of screening and surveillance intervals for diverticulosis patients. Methods . In this retrospective single-center study, patients diagnosed with diverticulosis on colonoscopy over a 10-year period were included. Each diverticulosis patient was matched with 1 control by age, gender, setting (inpatient/outpatient), and procedure's indication. CRC and polyp detection rates were recorded and compared between the groups before and after adjustment for bowel preparation quality and exam completion. CRC location was recorded and compared between groups. Results . A cohort of 13680 patients (6840 patients with diverticulosis and 6840 matched controls) was included. Diverticulosis was located mainly to the sigmoid and left colon (94.4%). The CRC diagnosis rate was lower in the diverticulosis group (2% vs. 4.5%, odds   ratio = 0.472, P < 0.001, and 95 % CI = 0.382 ‐ 0.584 ). Moreover, location of CRC was unrelated to diverticulosis location, as more CRCs in the diverticulosis group were located proximal to the splenic flexure as compared to the control group (42.5% vs 29.5%, respectively; P = 0.007 ). Diverticulosis, however, was associated with an increased polyp detection rate compared to controls (30.5% vs. 25.5%; odds   ratio = 1.2, P < 0.001, and 95 % CI = 1.11 ‐ 1.299 ). Conclusion. We demonstrated that diverticulosis was not associated with an increased risk for CRC. A possible increased polyp detection rate, however, warrants further evaluation in large prospective studies.